Brazilian Trade Unions: In (In)Voluntary Confinement of the Corporatist Past - Lang, Karen; Gagnon, Mona-Josée (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2009)
Many analysts of Brazilian industrial relations share a determinist vision of the country’s trade unionism, according to which the unions maintain a paradoxical yet atavistic relationship with the heavy body of laws that provide them with advantages while limiting their freedom. We tested this vision by conducting field enquiries into the daily activities of two Brazilian unions: the ABC Metalworkers Union and the Seamstress Union for the Sao Paulo and Osasco Region. In this article, we present the results of our case studies and what they reveal about Brazilian trade unionism’s relationship with the labour legislation. We also briefly discuss former trade union leader and current President Lula’s recent attempts to reform the country’s labour relations system.